Correlation of Nutritional Status, HbA1c, and Duration of Diabetes Mellitus with Amputation Incidence in Patients with Diabetic Foot Ulcers (Majalah Kedokteran Bandung, 2025)
Diabetic foot ulcer (DFU) is a severe complication of diabetes that significantly impairs quality of life and  may often lead to amputation, particularly when infections become extensive. This study investigated the correlation of nutritional status, HbA1c levels, and duration of diabetes exposure with the incidence of amputation in DFU patients. Using an observational analytic study with a retrospective cohort design, data from 47 DFU patients treated at the Vascular and Endovascular Surgery clinic and Emergency Room  of a hospital from 2019-2024 were analyzed. The majority of subjects were men aged 40-60 years (59.57%). Among the amputee group, 55.31% experienced neuropathy, primarily classified as Wagner's degree 4. Patients requiring amputation had significantly higher levels of urea, creatinine, and leukocytes compared to those who did not. A significant correlation was observed between the incidence of amputation and nutritional statusâ€”specifically, serum albumin (r=-0.616) and Body Mass Index (BMI) (r=0.823)â€”as well as HbA1c levels (r=0.806) and duration of diabetes exposure (r=0.445) (p
Keywords: Amputation; diabetes mellitus; diabetic foot ulcer; HbA1c; nutritional status